2020
DOI: 10.1186/s12891-020-3056-4
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose-derived Mesenchymal stem cells, low-intensity pulsed ultrasound, or their combination for the treatment of knee osteoarthritis: study protocol for a first-in-man randomized controlled trial

Abstract: Background Human adipose-derived Mesenchymal stem cells (HADMSCs) have proven their efficacy in treating osteoarthritis (OA), in earlier preclinical and clinical studies. As the tissue repairers are under the control of mechanical and biochemical signals, improving regeneration outcomes using such signals has of late been the focus of attention. Among mechanical stimuli, low-intensity pulsed ultrasound (LIPUS) has recently shown promise both in vitro and in vivo. This study will investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…More research is needed to define the electrophysiological properties of individual ion channels that can participate in mechanically altered metabolism of chondrocytes. The molecular mechanisms by which mechanical stimuli prevent articular cartilage degeneration and promote articular cartilage repair may yield insights into the rationale of possible mechanical therapy, such as the potential for therapeutic low-intensity pulsed ultrasound for OA [ 169 , 170 ].…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to define the electrophysiological properties of individual ion channels that can participate in mechanically altered metabolism of chondrocytes. The molecular mechanisms by which mechanical stimuli prevent articular cartilage degeneration and promote articular cartilage repair may yield insights into the rationale of possible mechanical therapy, such as the potential for therapeutic low-intensity pulsed ultrasound for OA [ 169 , 170 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on acoustic pressure equations and t the effective radiation area (ERA) of the probe, the interference of the acoustic waves in the environment was modeled. The texture characteristics are including density, speed of sound and attenuation coefficient with 993.37 kg/m 3 , 1528 m/s and 0.025 Np/m MHz in water 37 °C and 1090 kg/m 3 , 1615 m/s, 4.02 Np/m.MHz in skin tissue 35–37 °C, respectively 17 . Then based on the wave interference scheme, the axial transverse profiles of the acoustic pressure in the resulting cylindrical coordinates are solved in programming FORTRAN (Intel Visual Fortran Composer XE 2011) With PC with Core i5-4200 MCPU-2.50 GHz–6 GB RAM.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it is necessary to examine the function of the ultrasound to be able to approach the therapeutic goals and reach an ideal knowledge of ultrasound function. The mechanical index represents the threshold for acoustic cavitation 17 19 . Since ionizing radiation delays the production of inflammatory cytokines in the skin tissue and reduces the healing period of damage, in this study, stem cells were used along with ultrasound waves to enhance the cumulative effect of the therapy procedure.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that MSCs can effectively accelerate the repair of cartilage defects [96]. Numerous clinical trials [97][98][99][100][101][102][103][104][105] have been performed in this field that some of them mentioned in Table.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%